Calcification in coccolithophores: Effects of environmental conditions and paleoproxy calibrations - Müller, Marius N. (Christian-Albrechts-Universität zu Kiel, 2009)
Oceanic production of organic carbon and calcium carbonate by marine flora and fauna 'play' a major role in the Earth's cycling of carbon and calcium. Coccolithophores, as a major phytoplankton group, are involved in both cycles and are relevant in the regulation of the seewater calcium carbonate saturation state since the Mesozoic (251 million years ago). The present thesis investigates the influence of various environmental parameters on the physiology of coccolithophores, focusing on the process of biogenic calcification in regard to variations in the ocean's calcium and magnesium concentrations, as well as to changes in the macronutrient concentrations and in the seawater carbonate chemistry (ocean acidification).